Identifying the level of flexibility, speed and agility among visually impaired students / Borhan Yusof, Nagoor Meera Abdullah and Hisam Che Mat - Abdullah, Nagoor Meera; Che Mat, Hisam (Research Management Institute (RMI), 2010)
Visually impaired and blindness can cause low level of physical capacity, posture problems, orientation difficulties, depressions and problems with balance. Previous studies had indicated that these problems existed among the visually impaired and Visually impaired and blindness . Zabriske and McCormick (2001) defined visually impaired individual as having a limited field of vision either in a tunnel vision stage where the individual have the capability to see limited light source or can detect a minimal light source that aid them in finding direction. According to Ellis (2001) and Palmer (2006), visual impairment referring to individual that have the field of vision at the rate of 40% due to different congenital eye diseases that have a very minimal mobility capacity. Therefore, the needs to do research study on the fitness levels of the visually impaired in Malaysia is crucial since there are limited data in this area especially those related to the motor abilities of the handicapped individuals. Most of the studies done in this area are related to the education development of the VI and TB which focus on the educational instructions, visual aids apparatus, program structures and mainstream programming. However, there are no studies focus on the fitness levels of the VI and TB especially those measuring the level of flexibility, speed and strength of the handicapped individuals …